Historical Characterization of Sorghum Grain Filling Dynamics - J. Grünberg; A. J. P. Carcedo; P. A. Demarco; L. Mayor; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2022)
Understanding crop response to manipulations in source (number of leaves) and sink (panicle) during the growing season provides useful information to develop crop breeding strategies. In the present study, we assessed how source-sink manipulation can affect sorghum (Sorghum bicolorL.) yield and its components—grain number and grain weight (including grain filling dynamics)—for hybrids released in the past 60 years. The field experiment was conducted during the 2021 growing season in Wamego, KS (US), testing six commercially available grain sorghum hybrids released between 1963 and 2020. Grain weight significantly decreased from 28 to 21 mg in defoliation treatments among hybrids over time; and reached a maximum value of 34 mg when panicles were halved (P<0.05). For the control scenario, yield consistently increased over time (P<0.01). When source-sink treatments were applied, there was a reduction of 33 bu/a for the defoliation and 39 bu/a for the panicle halving (P<0.001). Regarding grain number per unit area, the trend was similar across hybrids over time (P<0.1) but decreased with the panicle halving to 1600 grains on average (P<0.001) relative to both control and defoliation scenarios. Over time and across source-sink treatments, there was no significant change in grain filling rate. However, a significant reduction for the duration of the grain filling was documented for defoliated plants, with a greater decrease over time.
Keywords: sorghum; source-sink; breeding; grain filling; grain weight